First year students'construction of an academic identity in English as a foreign language - Angels Oliva Girbau; Marta Milian Gubern (Universitat Politècnica de València, 2013)
This paper studies the construction of an academic identity through writing in English as a foreign language, using a theoretical approach based on socio-constructivism, genre theory, systemic-functional linguistics and cultural-historical activity theory. Specifically, we study the relationship between academic genres and identity in first-year Humanities students, and to what extent a reflective social approach to writing instruction can foster students' initiation by providing spaces to analyse and discuss the nature of the academic activity system. The theoretical underpinnings present students' identity in construction as an essential element in the process of acquisition of academic genres, hence key to students' success at university, and students' identities as key elements of the academic activity system, at the same level as the other three -its communication tools, users, and goals. The theoretical framework guided the design of a course on academic English as a foreign language for first-year Humanities students at Universitat Pompeu Fabra. The course materials were used simultaneously as research tools to gather the data for the study, using an emic perspective as a teacher/researcher. The results show a close relationship between students' problems with the acquisition of genres in English and conflicts between their identities and other elements of the academic activity system, particularly their relation to other members and to ideational content, and hence students' inability to make relevant contributions due to problems using academic genres in English.